Bioethical Implications of Dental Malpractice and its Relationship with Education (2017)
Purpose: This article is a bibliographic review and emphasizes that dental practice as a health profession in Mexico has a specific ethical and legal framework, which promotes the development of students in a climate of respect for an optimal practice of the profession so that students do not incur dental malpractice after graduating from their educational institutions. Period, origin and types of publications: The review covered the period between January 2012 and September 2014 as a research basis for the dissertation of a master’s degree in bioethics at the esm of the ipn, using documentary bibliographic information and scientific articles. Point of view: It is of the utmost importance that the training of the dental surgeon include scientific, technical and humanistic knowledge, such as responsibility, respect, beneficence, non-maleficence and justice, which are necessary for an appropriate practice. Finally, the need to strengthen a bioethical culture in students is proposed, making students aware of the sense of responsibility, respect and the value of life and building values that contribute to a cultural change of dental humanism.